O repórter no processo de inovação nos veículos tradicionais de mídia escrita - Fernandes, Daniel Lopes (2020)
This paper aims to investigate the role that the reporter plays, or imagines to play, in the eventual innovation processes in traditional media companies. The importance of this dissertation lies precisely in the fact that the exploration of the role of the reporter by the Brazilian academy is profound in its day-to-day life, but still arid in the discussion about the reporter's role (is there a role to play?) in the enormous challenge that these companies face: to reinvent (innovate). For that, a theoretical revision was made regarding concepts of innovation, innovation in the media and the skills, old and current, necessary to the reporter and, in order to fulfill the initial objective, will be adopted the qualitative method, with interviews semi-structured interviews with at least two editors, and the quantitative method, with 57 valid interviews with reporters. From the managerial and academic point of view, the present work intends to leave as contribution the beginning of a discussion on how to insert all the layers of production in processes that investigate means of transformation of these journalistic companies.